Indium-promoted znZrOx/nano-ZSM-5 for efficient conversion of CO2 to aromatics with high selectivity. Issue 3 (June 2022) - Xin, Qing; Guo, Hongyu; Wang, Yongchao; Xiao, Linfei; Wang, Wei; Wu, Wei
Abstract: The hydrogenation of CO2 to produce liquid hydrocarbons is an effective method for its resource utilization. However, due to the chemical inertness and multipath conversion of CO2, it is still a great challenge to efficiently convert CO2 to high value-added aromatic hydrocarbons. In this work, InZnZrO x and In-ZnZrO x samples with the same In2 O3 content (10 wt%) were prepared by the co-precipitation and the incipient wet impregnation method, respectively. Nano-ZSM-5 zeolite was synthesized by a seed-induced template-free method. The bifunctional catalysts prepared by physically mixing InZnZrO x and nano-ZSM-5 zeolite can achieve aromatics selectivity of 90.6% (the proportion of tetramethylbenzene is 69.5%) among all hydrocarbons at a CO2 single-pass conversion of 13.8% under optimized reaction conditions of 3.0 MPa, 4000 mL·gcat. −1 ·h −1, H2 /CO2 volume ratio of 3 and 320 °C. The selectivities to CO and CH4 are only 19.8% and 0.19%, respectively. Experimental results indicated that the formation of abundant oxygen vacancies and basic sites, achieving electron transfer from In and Zn ions to Zr ion, and improving mass transfer of nano-ZSM-5 zeolite results in the highest activity and aromatic selectivity over the InZnZrO x /nano-ZSM-5 bifunctional catalyst. This work provided a highly efficient way for direct CO2 hydrogenation to tetramethylbenzene. Graphical Abstract: ga1 Highlights: More oxygen vacancies were generated on the InZnZrO x solid solution prepared by co-precipitation method. In-promoted ZnZrO x samples have increased basic site densities. Rapid formation and further conversion of intermediate methoxy (CH3 O*) is beneficial to improve CO2 conversion and aromatics selectivity. Conversion of CO2 to aromatics with high selectivity of 90.6% achieved over a InZnZrO x /nano-ZSM-5 bifunctional catalyst. Nano-ZSM-5 zeolite is more favorable for the formation of multymethylbenzene than micro-ZSM-5 in the CO2 conversion reaction.